2019
DOI: 10.1177/2059204319893179
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging Attention and Exploration in a Hybrid Recommender System for Libraries of Unfamiliar Music

Abstract: There are few studies of user interaction with music libraries comprising solely of unfamiliar music, despite such music being represented in national music information centre collections. We aim to develop a system that encourages exploration of such a library. This study investigates the influence of 69 users’ pre-existing musical genre and feature preferences on their ongoing continuous real-time psychological affect responses during listening and the acoustic features of the music on their liking and famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…But our particular interest here was whether any of the prior expressed participant preferences could predict the response mechanisms they used. In the recommender system development and analysis during which the present data set was obtained (Taylor & Dean, 2019, 2021, we indeed found that prior expressed preferences for certain musical features (such as "bass," see Method) were useful for making successful recommendations within our set of unfamiliar pieces. We also found then that diversity of taste among a set of genre preferences was effective in predicting the range of "unusualness" within our musical excerpts that an individual would find acceptable (and give a relatively high liking score).…”
Section: Continuous Affect Responses: Bayesian Analysismentioning
confidence: 65%
See 4 more Smart Citations
“…But our particular interest here was whether any of the prior expressed participant preferences could predict the response mechanisms they used. In the recommender system development and analysis during which the present data set was obtained (Taylor & Dean, 2019, 2021, we indeed found that prior expressed preferences for certain musical features (such as "bass," see Method) were useful for making successful recommendations within our set of unfamiliar pieces. We also found then that diversity of taste among a set of genre preferences was effective in predicting the range of "unusualness" within our musical excerpts that an individual would find acceptable (and give a relatively high liking score).…”
Section: Continuous Affect Responses: Bayesian Analysismentioning
confidence: 65%
“…Acoustic features were extracted using a combination of standard Max objects, for example, fft ∼ and fzero ∼, third-party externals such as zsa.descriptors (Malt & Jourdan, 2008), Alex Harker externals (Harker, 2017), and CNMAT external objects (from the University of California, Berkeley). A complete list of acoustic features, together with an explanation of their unit output is shown in Table 1 (these are described in more detail in Taylor & Dean, 2019).…”
Section: Participants Materials Experimental Method and Proceduresmentioning
confidence: 99%
See 3 more Smart Citations